Analisis Efisiensi Ekonomis Usahatani Padi Sawah di Desa Tebing Tinggi Kecamatan Benai Kabupaten Kuantan Singingi - Ansori, Rizal; Tety, Ermi; Eliza, Eliza (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Tebing Tinggi Village in Benai District, Kuantan Singingi Regency is one of the rice farming centers in the region. In 2023, rice production in this village decreased to 480.00 kg from 589.26 kg in 2022. This study was conducted on 30 farmers who cultivated the Cisokan rice variety, using the Cobb-Douglas analytical model processed with SPSS version 23. The objectives of the study were to identify the characteristics of rice farmers, and evaluate the economic efficiency of rice farming in Tebing Tinggi Village. The results showed that most farmers were aged between 40 and 60 years (96.7%), had farming experience ranging from 15 to 27.5 years (66.7%), had an elementary school level of education (53.4%), and an average household size of three members (43.4%). Furthermore, the efficiency analysis showed that all production factors used were not yet economically efficient, as indicated by an efficiency index value greater than 1. Therefore, the use of improved seeds, urea fertilizer, and labor needs to be increased to achieve economic efficiency. Technical efficiency is achieved when input use maximizes output, while allocative efficiency is reached when the marginal value product equals the input price. Economic efficiency is attained when both technical and allocative efficiencies are met.